Gram-negative bacteria resist antimicrobial agents by a DzrR-mediated envelope stress response - Liang, Zhibin (2023)
Background: Envelope stress responses (ESRs) are critical for adaptive resistance of Gram-negative bacteria to envelope-targeting antimicrobial agents. However, ESRs are poorly defined in a large number of well-known plant and human pathogens. Dickeya oryzae can withstand a high level of self-produced envelope-targeting antimicrobial agents zeamines through a zeamine-stimulated RND efflux pump DesABC. Here, we unraveled the mechanism of D. oryzae response to zeamines and determined the distribution and function of this novel ESR in a variety of important plant and human pathogens. Results: In this study, we documented that a two-component system regulator DzrR of D. oryzae EC1 mediates ESR in the presence of envelope-targeting antimicrobial agents. DzrR was found modulating bacterial response and resistance to zeamines through inducing the expression of RND efflux pump DesABC, which is likely independent on DzrR phosphorylation. In addition, DzrR could also mediate bacterial responses to structurally divergent envelope-targeting antimicrobial agents, including chlorhexidine and chlorpromazine. Significantly, the DzrR-mediated response was independent on the five canonical ESRs. We further presented evidence that the DzrR-mediated response is conserved in the bacterial species of Dickeya, Ralstonia, and Burkholderia, showing that a distantly located DzrR homolog is the previously undetermined regulator of RND-8 efflux pump for chlorhexidine resistance in B. cenocepacia. Conclusions: Taken together, the findings from this study depict a new widely distributed Gram-negative ESR mechanism and present a valid target and useful clues to combat antimicrobial resistance.